Economic Analysis for Replacement of 11kV overhead Koteshwor Feeder by Underground Distribution System - Sah, Ganesh Kumar; Poudel, Laxman (Journal of Advanced College of Engineering and Management, 2021)
Cost effective, Aesthetic and Reliable energy supply is the need of any mankind. In this study, economic analysis for replacement of 11 kV overhead distribution feeder by 11kV underground cable is done with reference to Koteshwor Feeder under Baneshwor Distribution and Consumers Service. The reliability indices like SAIDI, SAIFI, ENS etc. is performed by using DigSilentPowerFactory software. The reliability of overhead distribution system is evaluated by using real system data system and similarly, historical IEEE standard data is used for underground distribution system. The reliability indices are compared for both distribution systems. Result shows that interruption in the overhead system is more than underground distribution system, the energy not supplied to the customer by overhead distribution system is also more than underground distribution system. The replacement cost estimation is performed by using Nepal Electricity Authority (NEA) unit rate and KEI industries quoted price for NEA underground project. The B/C ratio and Present Worth value for the 25-year period of useful life shows that the replacement of the existing overhead distribution system by underground distribution system is financial suitable and can be payback by revenue save from the Energy Not Supply (ENS) lower value of underground distribution system than overhead distribution system. In order to get the continuous of supply, esthetic and public safety in electricity distribution field one may have to bear initially extra cost to use underground distribution systems which finally get payback. Thus, in case of densely populated city like Kathmandu, underground distribution system is reasonable requirement for continuous supply, esthetic and public safety in electricity distribution filed.